(untitled) (Fiep Bulletin - online, 2014)
The frequency of the use of licit drugs have highlighted factors like religiosity, working conditions, studies, influence of friends or relatives, psychosocial factors as conflicts with parents, negative feelings and loneliness with the use of alcohol and tobacco. This is a study based on research conducted in the field, on the licit drugs use by young people in the city of São Paulo, emphasizing the use of alcohol and tobacco, held in the months of March to May 2013. We analyzed the use of alcohol and tobacco by young people, adults and subgroups at greatest risk, to submit the form which interferes in the style of life of the individual and of his family. Meet the consequences that could entail, check the toxic effects that cause to the individual, the risks to Public Health in general. It was observed that the majority of users are teenagers between 18 and 24 years old, of those surveyed females predominated in tobacco use. The drugs most consumed by teenagers from 13 to 15 years old (43%) is the cigarette and from 15 to 18 years old (41%) alcohol.90% of respondents use licit drugs, 42% started using out of curiosity, 75% with friends when using for the first time. The damage by the use of the cigarette evinced: 52% morning cough, 37% nervousness and other factors, 62% reported to have tried to quit smoking, 75% of users reported not having tobacco intention to quit smoking, 56% of respondents live with smokers. The damage caused by the use of alcohol reported: a small proportion of respondents related losses of memory and learning under effect of alcohol, behavioral and emotional changes, 60% of respondents are children of parents who consume alcohol, a given alarming is that 44% of respondents take a ride with friends who made use of the alcohol. It was noted in the study that the greatest risks are for young people 18 to 24 years old and that women are the most consuming licit drugs. Being so, the assistance of public and private networks is necessary for the dissemination of harm caused by these licit drugs, thus contributing to promote the reduction of these fees that are currently very high.